Hubungan Pola Makan dan Konsumsi Kopi Dengan Kejadian Gastritis pada Dewasa di UPT Puskesmas Pagar Merbau 2026 - Paul Saut Marganda Tobing (Universitas Methodist Indonesia, 2026)
Gastritis is an inflammation of the gastric mucosa that remains a common health problem among adults, often associated with irregular dietary patterns and excessive coffee consumption. This study aimed to analyze the relationship between dietary patterns and coffee consumption with the incidence of gastritis among adults at UPT Puskesmas Pagar Merbau, Deli Serdang Regency, using a quantitative cross-sectional design with 30 respondents selected through purposive sampling. Data were collected using a validated and reliable questionnaire and analyzed using univariate and bivariate methods with Spearman’s rank test. The results indicated that most respondents had poor dietary patterns (60.0%), high coffee consumption (66.7%), and severe gastritis (83.3%). Bivariate analysis revealed significant relationships between dietary patterns (r = 0.531; p = 0.003) and coffee consumption (r = 0.441; p = 0.015) with the incidence of gastritis, with moderate strength and positive direction. This indicates that poorer dietary patterns and higher coffee consumption are associated with more severe gastritis. Therefore, maintaining regular dietary habits and limiting coffee consumption are important preventive measures.